Indonesia Strategi Sosialisasi Komisi Pemilihan Umum Kota Administrasi Jakarta Timur pada Pemilu Inklusif Tahun 2019 - Shavira, Chelsy; Firman, Firman (Journal of Politics and Democracy, 2022)
The implementation of the 2019 Inclusive General Election was faced with several problems related to limited communication, voter data, logistical problems and vote counting problems, as well as efforts to increase community participation. This becomes a task for the general election organizers, namely the general elections commission to conduct socialization in order to increase public participation and fulfil facilities in the implementation of inclusive general elections. Inclusive elections are intended for persons with disabilities with the aim of providing equal rights and facilities and increasing voter participation of persons with disabilities. By making a socialization strategy in the 2019 election which aims to increase public participation in the 2019 general election. In this study the method used is the qualitative research method with a phenomenological approach and data collection techniques using direct interviews and literature studies of the implementation of socialization in the east Jakarta administration city has several theoretical applications, such as socialization theory, general election theory, participation theory and socialization strategies to increase public participation in the implementation of general elections and also to provide access to election facilities for people with disabilities. The implementation of socialization and fulfilment of facilities in the east Jakarta administration city has been going quite well and also obtained satisfactory results on the participation of the voting community.